KIIPF - An integrated inter-operable knowledge management process framework for healthcare: Implementation in Pakistani healthcare industry - Noordin, Mohamad Fauzan; Arshad, Arfan; Othman, Roslina (IGI Publishing, 2017)
Being complex systematically, Knowledge Management (KM) has always been challenging in the healthcare industry (HCI) of developing countries like Pakistan due to gap in acquiring and implementing KM processes. Despite the fact that extensive data and related information is available, the Pakistani HCI has been facing a major challenge due to the absence of a sound and solid KM process framework. Hence, the existing healthcare information systems in Pakistan lack the ability to control and cater the diversified nature of new knowledge creation and innovation. Consequentially, it results in inefficient and ineffective organization of knowledge along with inability to properly utilize important resources that are used for decision making activities. In this study, the researchers present and suggest an integrated and inter-operable KM process framework that helps to streamline and integrate a KM process in a phased comportment that identifies, defines, analyzes, collects and manages knowledge along with its innovation, dissemination, sharing and storage in an appropriate way.